Cajanin Stilbene Acid Inhibited Vancomycin-Resistant Enterococcus by Inhibiting Phosphotransferase System - Tan, Shengnan; Hua, Xin; Xue, Zheyong; Ma, Jianzhang (Frontiers in Pharmacology, 2020)
Antimicrobial resistance has become a serious threat to human and animal health, and vancomycin-resistant enterococcus has become an important nosocomial infection strain, causing thousands of deaths each year. In this study, after screening a variety of natural products, we found that CSA had significant significant inhibitory effect on sensitive and vancomycin-resistant enterococcus, and in vivo experiments, we also confirmed that CSA had significant anti-VRE infection ability. Subsequently, we studied the antibacterial mechanism of CSA through proteomics experiments, and the results showed that CSA killed enterococcus by inhibiting the phosphotransferase system of enterococcus, thus hinders the normal growth and metabolic functions of bacteria. The results of this study provided evidence for the in-depth study on the mechanism of the antibacterial action of CSA and also provided a candidate for the development of anti-VRE drugs.